Are Global University Ranking Tables Still Valued in China? - Huang , Futao; Postiglione , Gerard (International Higher Education, 2022)
The suitability of global university rankings for China’s national conditions and the institutional character of its universities is currently being reconsidered. Three leading universities have opted out of the rankings. However, there is no clear evidence to show that this is part of a wider trend. Western rankings are still valued and used as a means to attract high-level talent and bestow a world-class brand on more Chinese universities and disciplines.